Identification and quantification of limonoid aglycones content of Citrus seeds - Montoya,Carlos (2019)
ABSTRACT Citrus fruits are recognized as an important source of bioactive molecules such as limonin and nomilin. However, these molecules exhibit low bioavailability, therefore, obtaining these molecules using biotechnological techniques may be an alternative to harvesting them directly from fruits. The aim of this study was to quantify and identify limonoids in the dichloromethane extracts of Citrus seeds of Criolla orange, Oneco tangerine, Tangerine-lemon, Sour orange and Valencia orange from department of Antioquia-Colombia by high performance liquid chromatography with diode array detection, and high-resolution mass spectrometry. Although in all the samples total glycosidic free limonoids were present, Oneco tangerine seeds had the highest concentration, followed by Tangerine-lemon seeds, equivalent to 0.75% and 0.53% per total dry weight, respectively. These results suggest Oneco tangerine seeds may be used as an elite material for biotechnological processes looking for increased production of limonoids to support research and drug development.